2015
DOI: 10.3168/jds.2014-8987
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forage type and extruded linseed supplementation on methane production and milk fatty acid composition of lactating dairy cows

Abstract: Replacing dietary grass silage (GS) with maize silage (MS) and dietary fat supplements may reduce milk concentration of specific saturated fatty acids (SFA) and can reduce methane production by dairy cows. The present study investigated the effect of feeding an extruded linseed supplement on milk fatty acid (FA) composition and methane production of lactating dairy cows, and whether basal forage type, in diets formulated for similar neutral detergent fiber and starch, altered the response to the extruded linse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
30
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 40 publications
9
30
2
1
Order By: Relevance
“…In a meta-analysis, Patra (2013) indicated CH 4 emission to be affected by the amount of C18:3, a major component in linseed oil, but demonstrated that the CH 4 -suppressing effect might be more marked with high concentrations of non-fiber carbohydrates in diets. However, Livingstone et al (2015) did not find a decrease in CH 4 emission upon linseed supplementation regardless of the ratio of grass silage to corn silage in the diet of dairy cattle. Various non-fiber carbohydrates may yield different VFA proportions, which makes it difficult to explain the CH 4 -suppressing effect of C18:3 in detail.…”
Section: Discussionmentioning
confidence: 92%
“…In a meta-analysis, Patra (2013) indicated CH 4 emission to be affected by the amount of C18:3, a major component in linseed oil, but demonstrated that the CH 4 -suppressing effect might be more marked with high concentrations of non-fiber carbohydrates in diets. However, Livingstone et al (2015) did not find a decrease in CH 4 emission upon linseed supplementation regardless of the ratio of grass silage to corn silage in the diet of dairy cattle. Various non-fiber carbohydrates may yield different VFA proportions, which makes it difficult to explain the CH 4 -suppressing effect of C18:3 in detail.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, increasing grass maturity increases NDF concentration and acetate is a major end product of NDF fermentation, with acetate production enhancing methane formation (Johnson and Johnson, 1995). Studies have reported decreased methane emission from ruminants when replacing GS with MS (Reynolds et al, 2010;Brask et al, 2013;van Gastelen et al, 2015), although some have reported no effect (Staerfl et al, 2012;Livingstone et al, 2015), and thus more research is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, nitrate (2.2%) did not reduce CH 4 emissions in finishing beef cattle fed a high concentratebased diet as these animals were already low CH 4 -emitters (Troy et al, 2015). The CH 4 -mitigating effect of linseed was also not observed in studies in which the level of FA in diets was low (1% to 2% of DM; Livingstone et al, 2015) or not different from their control diet, which contained a rumen inert fat source (Van Zijderveld et al, 2011a;Veneman et al, 2014). We observed a severe CH 4 -mitigating effect of LIN + NIT just after feeding, which was most probably linked to the effect of quickly metabolised nitrate in the rumen.…”
mentioning
confidence: 97%